Periphery of Practice: Chinese Immigrant Women Navigating the Canadian Labour Market - Hongxia Shan (Adult Education Research Conference, 2006)
This paper proposes periphery of practice as a conceptual lens to examine the learning experiences engaged by Chinese immigrant women navigating the Canadian labour market.
Keywords: Periphery of practice; immigrant women; occupational orientation; mediation of learning; meaning negotiation